Pemberdayaan Perempuan Pesisir Melalui Pelatihan Pengolahan Hasil Laut Guna Meningkatkan Jiwa Wirausaha Desa Banyusangka, Bangkalan - Hasanah, Uswatun; Ferdian Ramadhani, Ahmad; Hafid Ahsani, Abdul; Sayidina Mukti, Puan Pramesti; Nisa, Hikmiatin (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2025)
Banyusangka Village in Bangkalan Regency, East Java, has great potential in the field of fisheries, but the processing of marine products still lacks innovation. Therefone, the Real Work Lecture (KKN) Activity of Group 07, Trunojoyo Madura University, conducted training on processing marine products for the Women Empowerment and Family Welfare (PKK) group in Banyusangka Village. The training was conducted through cooking demonstrations and hands-on practice of making Surimi fish nuggets from Tuna. The results showed that the PKK women were enthusiastic and interested in making and selling processed marine products. Thus, this training can enhance entrepreneurial spirit and open new business opportunities for the PKK women in Banyusnagka Village. This activity is expected to improve the community’s economy and serve as an example for other coastal villages. Through this training, the community of Banyusangka Village can utilize the existing fisheries potential to improve their economic welfare.